Mathematical Literacy: Ethnomathematics in PISA Leveling Representations - Nila Ubaidah; Zaenuri Zaenuri; Iwan Junaedi; Sugiman Sugiman (Universitas Negeri Semarang, 2022)
Mathematical literacy is logical reasoning in solving mathematical problems. But over time, the meaning of mathematical literacy also develops and is often associated with a person's ability to identify and understand problems in which mathematics plays a role in all areas of life. The purpose of this study is to represent Mathematics Literacy Problems in PISA leveling associated with ethnomathematics and can be used as examples to deliver teaching materials in schools. The research used is a qualitative descriptive study with the object of research is the Culture of the Kutai Society, which is represented in the Mathematical Literacy problem of the PISA Socio-Cultural Context Model. From the research, it was found that the Technique of Designing PISA Model Mathematical Literacy Questions Using the Socio-Cultural Context of the Kutai Community contained 3 things in designing the PISA model grids and math problems based on argumentation indicators. The problem design process is carried out by prototyping using three characteristics, namely content, construct, and language.